Wet torrefaction of biomass for high quality solid fuel production: A review. (August 2018) - He, Chao; Tang, Chunyan; Li, Chuanhao; Yuan, Jihui; Tran, Khanh-Quang; Bach, Quang-Vu; Qiu, Rongliang; Yang, Yanhui
Abstract: Wet torrefaction (WT) is a sustainable subcritical water pretreatment technology to upgrade moist biomass into hydrochar solid fuel with superior fuel properties with the avoidance of energy-intensive conventional thermal drying. In order to obtain a holistic understanding of WT processing system, this review has comprehensively discussed recent advances in WT of biomass to produce high quality solid fuel and its subsequent thermochemical applications. This review has not only summarized distinct advantages of WT over dry torrefaction of biomass with high moisture content but also clarified the similarities and differences between WT and hydrothermal carbonization. According to structures and chemical compositions of components therein, four representative categories of diverse biomass materials were selected to describe the influence of intrinsic nature of biomass on fuel quality of hydrochar derived from WT. Furthermore, this article has attempted to figure out the inherent relationship between WT conditions and fuel properties with respect to operating conditions (e.g. temperature, pressure, and residence time), biomass to water ratio, acids and additives, torrefaction atmosphere, and heating techniques. Three conventional thermochemical applications of wet-torrefied biomass have been extensively reviewed to reveal that WT could benefit energy recovery from wet biomass in terms of improved quality of ultimate energy carriers and obviously reduced pollutants emissions. Nevertheless, critical concerns associated with optimization of operating cost, minimization and controlling of pollutants emissions, re-design of industrially applicable reactor, and system integration with downstream applications have been pointed out in order to make WT technology more environmentally and commercially viable. Graphical abstract: fx1 Highlights: Wet torrefactoin of biomass to superior solid fuel has been extensively reviewed. Effects of nature of biomass materials on mass and energy yields are discussed. Relationship between wet torrefactoin conditions and fuel properties is presented. Thermochemical applications of wet-torrefied biomass are analyzed.